The effectiveness of butterfly pea flower extract cream on collagen synthesis in post-dermapen wound healing - Fatimah, Aulia Nurul; Hutabarat, Bartimeus Nicomama; Chairul, Muhammad (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2024)
Skin wounds, whether acute or chronic, disrupt the integrity of the largest organ in the human body. The healing process involves intricate stages, with collagen playing a crucial role. Microneedling therapies, such as dermapen, stimulate collagen production and improve skin texture. This study investigated the effect of butterfly pea flower (Clitoria ternatea) extract cream on collagen production during the healing of dermapen-induced wounds in obese Wistar rats. Dermapen treatment, a minimally invasive cosmetic procedure, induces controlled skin punctures to stimulate collagen production. However, obesity can impair wound healing. This study aimed to determine if butterfly pea extract, rich in antioxidants, could enhance collagen synthesis and accelerate wound closure in obese rats. The results demonstrated that all treatment groups with butterfly pea extract cream exhibited significantly faster wound healing compared to the control group. Histopathological analysis revealed denser collagen deposition in the treatment groups, particularly those treated with 7% and 10% extract cream. These findings suggest that butterfly pea extract cream may have therapeutic potential in promoting efficient wound healing, particularly in obese individuals, by enhancing collagen production and accelerating the recovery process.